1715. Influenza-like Illness (ILI) Experience Among Healthcare Workers in Military Treatment Facilities: An Offshoot of the Pragmatic Assessment of Influenza Vaccine Effectiveness in the DoD (PAIVED) Study. (31st December 2020) - Colombo, Rhonda; Richard, Stephanie; Schofield, Christina; Collins, Limone; Ganesan, Anuradha; Geaney, Casey; Hrncir, David; Lalani, Tahaniyat; Markelz, Ana E; Maves, Ryan C; McClenathan, Bruce; Mende, Katrin; et al.
Abstract: Background: Healthcare workers (HCWs) are at heightened risk of exposure to respiratory pathogens. There are limited published data on influenza-like illness (ILI) experience among HCWs, and the few available studies were hampered by incomplete vaccination histories. PAIVED, a multicenter, multiservice study assessing influenza vaccine effectiveness in the Department of Defense, provides a unique opportunity to describe ILI experience among vaccinated HCWs compared to vaccinated non-HCWs. Methods: PAIVED participants were randomized to receive either egg-based, cell-based, or recombinant-derived influenza vaccine then surveyed weekly for ILI. At enrollment, participants provided key demographic data including whether they were HCWs with direct patient contact. ILI was defined a priori as 1) having cough or sore throat plus 2) feeling feverish/having chills or having body aches/fatigue. Participants with ILI completed a daily symptom diary for seven days and submitted a nasal swab for pathogen detection. Results: Of 4433 eligible participants enrolled during the 2019-20 influenza season, 1551 (35%) were HCWs. A higher percentage of HCWs experienced an ILI than non-HCWs (34% vs 26%, p< 0.001). Overall, HCWs were more likely to be female (42% vs 32%), age 25-34 years (39% vs 28%), active-duty military (81% vs 62%), non-smokers (88% vs 75%), and physically active (92% vs 85%). Self-reported race differed between HCWs and non-HCWs; a higher proportion of HCWs identified as White (63% vs 56%) or Asian (8% vs 5%). Similar demographic differences existed among HCWs and non-HCWs with ILI. HCWs were more likely to respond to at least 50% of weekly surveillance messages, irrespective of ILI status. HCWs with ILI had less severe lower respiratory symptoms (p< 0.001) and a shorter duration of illness (12.4±8.1 days vs 13.7±9.0, p=0.005) than non-HCWs. Pathogen data is pending. Conclusion: HCWs in PAIVED were more likely to report ILI than their non-HCW counterparts yet tended to have lower illness severity, possibly reflecting a higher level of baseline health or enhanced awareness of early ILI symptoms. The important epidemiologic position HCWs occupy for ILI has been apparent in the COVID-19 pandemic. Exploring ways to mitigate ILI risk in HCWs beyond influenza vaccination is warranted. Disclaimer Disclosures: All Authors : No reported disclosures